First record of the Nephropid genus Acanthacaris Bate, 1888 (Crustacea: Decapoda: Nephropidae) from Taiwan - Chang, Su-Ching; Wang, Teng-Wei; Chan, Tin-Yam (Zootaxa, 2015)
The giant deep-sea lobster genus Acanthacaris Bate, 1888 is reported for the first time from Taiwan. The single specimen with a total length of 36 cm was collected near a cold seep off southwestern Taiwan at about 1300 m deep and identified as A. tenuimana Bate, 1888.